Effect of Molecular Distortion of Ligand Field Splitting in Five-Coordinated Metal Complex. Issue 1 (April 2020) - Fujikawa, Yoshiki; Tsuneda, Dan; Tsutsumi, Yuki; Nakano, Momoe; Oguma, Takeyoshi; Ishii, Tomohiko; Sakane, Genta; Ogasawara, Kazuyoshi
Abstract: Metal complex indicates the significant physical properties such as magnetism, electrical conductivity and an optical property due to the electronic interaction between the ligand molecule and the central metal ion. We have evaluated the magnetism of the metal complex by controlling the ligand field splitting, which is the energy splitting of the d-orbitals. The magnetic phenomenon of such compounds are realized as a result of the electronic state based on the transition metal coordination complexes, and which can be switched between high spin (HS) and low spin (LS), that is called a spin-crossover (SCO) phenomenon. Our group have been investigated the way how to control the spin state according to the concept of a molecular distortion. The five-coordinated metal complex ML5 has been experimentally confirmed to be a molecular distortion called the Berry pseudorotation (BPR). In the BPR process, both the axial and equatorial ligands can move at the same rate of increasing the angle between the other axial or equatorial ligands in five-coordinated metal complex. The classical BPR mechanism changes its molecular symmetry between two independent trigonal bipyramidals (TBPs) of D3h symmetry via a square pyramidal (SP) of C4v symmetry. The distortion parameters in the five-coordinated metal complexes τ5 are proposed in order to represent the distortion of the BPR process quantitatively. In this work, we predicted the possibility of the SCO phenomenon in intramolecular exchange mechanism through the BPR process in a five-coordinated metal complexes.